Risk assessment for the importation of Bitumen for road construction into South Africa - Hanekom, Christiaan H. (Stellenbosch : Stellenbosch University, 2016)
ENGLISH ABSTRACT: The purpose of this research project was to identify, assess and model the risks associated with the importation of bitumen into South Africa. Bitumen has firmly established itself as a product which is not just essential to the construction and maintenance of roads, but also plays a key role as an economic driver of a country. In the years 2012 and 2013, South Africa was faced with a bitumen shortage estimated at 20% of the total production volume of the local industry. This was due to an untimely and unplanned shutdown of a refinery, causing disruption of the road construction industry of South Africa. Due to the unplanned shutdowns in 2012, COLAS – a South African bitumen supplier, imported 3849 metric tons of bitumen into Cape Town. After the operation the South African Bitumen and Tar Association (SABITA) published a document on the “Best practice guide for the procurement and importing of bitumen”. This document indicated that, even with risk management being the focal point of many activities and technologies, the risks associated with the importation of bitumen are not well known and documented. Furthermore, limited literature dealing with the international procurement of bitumen is available. This research project aims to assess and model the procedures and risks involved when importing bitumen into South Africa. The goal is to develop a structured guideline to determine and evaluate risks associated with the importation of bitumen. The guideline contains a procedural outline for the import of bitumen, as well as the identification and assessment of the associated risks. A system approach to the study of the import process was adopted. The system components were analysed and can be classified as physical, organisational and managerial components. The physical components of the system relate to the manufacturing, transporting and storage of bitumen. For the organisational component the different parties involved are discussed. The managerial components discussed are those for the financial, logistical, quality, safety, environmental and contractual management aspects. System related risks were identified by analysing the bitumen import system. Ten major sources of risk were analysed. The relative risk criteria were then determined, from which a risk breakdown structure was developed. Risks were then identified for each of the individual criteria. 75 risks were identified in total, with the risks being identified through literature and semi-structured interviews with industry related parties. It was established from the semi-structured interviews that intellectual property exists surrounding the quantification of the risks. The decision was made to analyse the risks by means of researching each individual risk, quantifying each based on expert knowledge gained from semi-structured interviews and studying academic literature. An industry professional from Australia was approached to give a second data set of quantified risks. The two data sets were used for the risk analysis. Risk analysis and modelling based on the fuzzy logic methodology was then done. The fuzzy logic methodology was deemed appropriate as the data sets comprised of data which could not be determined in a concise manner. The top 10 most significant risks were identified to be the following, (1) Product does not conform to specifications, (2) Viscosity changes of bitumen during transport, (3) Knowledge inadequacy, (4) Pollution in harbour during unloading, (5) Availability of product from other sources, (6) Unloading delay due to machine failure, (7) Unavailability of sufficient professionals and managers, (8) Inadequate project management controls, (9) Delay in solving contractual issues, and (10) Bad weather on open sea. It can be concluded that the importation of bitumen is a viable solution to deal with future bitumen shortages in South Africa, but requires expert logistic management and planning for the process to be a success.